A new approach to gene therapy using Sleeping Beauty to genetically modify clinical‐grade T cells to target CD19. Issue 1 (January 2014) - Singh, Harjeet; Huls, Helen; Kebriaei, Partow; Cooper, Laurence J. N.
Summary: The advent of efficient approaches to the genetic modification of T cells has provided investigators with clinically appealing methods to improve the potency of tumor‐specific clinical grade T cells. For example, gene therapy has been successfully used to enforce expression of chimeric antigen receptors (CARs) that provide T cells with ability to directly recognize tumor‐associated antigens without the need for presentation by human leukocyte antigen. Gene transfer of CARs can be undertaken using viral‐based and non‐viral approaches. We have advanced DNA vectors derived from the Sleeping Beauty (SB) system to avoid the expense and manufacturing difficulty associated with transducing T cells with recombinant viral vectors. After electroporation, the transposon/transposase improves the efficiency of integration of plasmids used to express CAR and other transgenes in T cells. The SB system combined with artificial antigen‐presenting cells (aAPC) can selectively propagate and thus retrieve CAR + T cells suitable for human application. This review describes the translation of the SB system and aAPC for use in clinical trials and highlights how a nimble and cost‐effective approach to developing genetically modified T cells can be used to implement clinical trials infusing next‐generation T cells with improved therapeutic potential.